STIM1 for stimulation of phagocyte NADPH oxidase - Ye, Richard D. (American Society of Hematology, 2014)
In this issue of Blood, Zhang et al show that mice lacking the stromal-interacting molecule 1 (STIM1) gene in bone marrow cells are more susceptible to bacterial infection but are resistant to ischemia/reperfusion injury because of defective activation of phagocyte nicotinamide adenine dinucleotide phosphate (NADPH) oxidase.(1)